Gamificação: Uma ferramenta para aumentar a frequência de atividade física em adolescentes com excesso de peso - Patricio, Diego Silva (2017)
INTRODUCTION: Researches associate time in front of the screen on childhood and youth with sedentary lifestyle, and in consequence, with overweight or obesity. Childhood obesity is a worldwide epidemic with metabolic repercussions across all age groups. With that, is also verified the presence of several comorbidities associated to this disease. Teenager’s fascination with digital games can be used to prevent and reduce obesity incidence though games that stimulate physical exercise. Studies present that this kind of games (exergames or active video games) have positive repercussions on lose weight and increased energy expenditure, but these games alone aren’t enough to keep teenagers on intervention programs for obesity treatment. The “Gamification” has been used as a strategy to increase the performance of a person on the acting of some tasks. OBJECTIVE: Build and test a Gamification protocol to increase physical activity frequency, thought active videogame on overweight teenagers in school environment. MATERIALS AND METHODS: In the first stage, an integrative review was made using a systemization from websites specialized in games for the selection of games (exergames) that were used in the intervention. The randomized intervention study involved 65 teenagers between 15 – 19 years of age with obesity / overweight who were allocated in two teams, 28 in the control team, who used the active video game for physical activity and 37 in the experimental team, who beyond the videogame, used a gamut protocol thought an application called Mettis Arena. A randomization about the kind of intervention was performed in the two selected schools. For the intervention, the XBOX 360 platform and the “just dance” game were used, since the game allows the individual to achieve a moderate intensity of exercise. The gamification consisted in the insertion of different elements as motivational factors, such as punctuation goals, virtual prizes, group competitions, progress of steps, among others. The gamification behavioral intervention was called “The Metis Arena” and is composed by a combination of engagement challenges specifically created for the intervention, and dance challenges in dance exergames. The teenagers in a four participants team, were submitted thought a physical activity with active videogame three times a week, being 50 minutes per session, totalizing 150 minutes of weekly activities for a period of four weeks, and those that belonged to the selected school for the gamification, had extra intervention activities with active videogame. The teenagers were measured at a starting point (week 0) and after the intervention (four weeks), with information on their attendance frequency and nutritional status assessed at the beginning and after the intervention. Statistical analysis was performed through 22.0 version of SPSS, with descriptive statistics being performed first thought absolute and relative frequency. The sociodemographic characteristics and nutritional status between the groups were compared at the initial and final moments by the chi-square test. This test was also used to compare the frequencies of physical activity among the group, as well as the association between gender, nutritional status and type of intervention and adherence to VGA activities. For all statistical analyzes, a significance level of 5% was adopted. RESULTS: About 65 of the teenagers evaluated, 12.4% were obese. The prevalence of obesity was significantly higher on B school, in which the intervention used only the active videogame and where the frequency of physical activity was lower, but the nutritional status was not related to adhesion. The 75% frequency or more in the gamma intervention was associated with a higher frequency of the teenagers to physical exercise. The adhesion to physical exercise by the teenagers was not associated with the initial nutritional status, but it was associated with the kind of intervention. CONCLUSION: The gamification has proved effective in increasing adherence in teenager’s participants in weight loss programs, but requires longer duration studies to evaluate the impact for weight loss.